Post-exercise Hypothermia Varies Between High- and Low-Altitude Populations in the Asiatic Toad (Bufo gargarizans) - Yao, Zhongyi; Huang, Kun; Qi, Yin (Frontiers in Ecology and Evolution, 2022)
Whether and how poikilothermic animals change their thermal performance to cope with global warming are crucial questions to predict the future of biodiversity. Intraspecific comparison among populations that occur in different climatic zones can provide insight into how poikilotherms may alter their thermal performance under a particular climatic event. We compared populations of the Asiatic toad (Bufo gargarizans) from two altitudinal zones (3239 m and 926 m above sea level) to explore variations of post-exercise hypothermia, which can lead to lower temperature preference than normal conditions. Common garden experiment was also employed to test plasticity of hypothermic performance in adult toads. As results, exhaustive exercise induced measurable reduction in body temperature for both populations. Furthermore, high-altitude population experienced larger reduction in body temperature than low-altitude conspecifics in both original habitat and common garden conditions. Therefore, low-altitude toads may to enhance their hypothermic reaction if they shift their ranges to higher altitudes to survive warming climate; However, the relatively limited plasticity of hypothermic performance may constraint their adaptative process.